Tomato fruit quality and nutrient dynamics under water deficit conditions: The influence of an organic fertilizer - Maryam Zahedifar; Ali Akbar Moosavi; Edris Gavili; Arash Ershadi (PLoS ONE, 2025)
Drought adversely affects the growth and performance of plants. By contrast, the application of organic modifiers can improve plant growth by supplying nutrients and water. The influence of foliar application of organic fertilizer under water deficit conditions on growth traits, chemical composition, and fruit quality of tomato (Lycopersicon esculentum Mill., var. Maya) were investigated in greenhouse conditions based on bi-plot and principal component analysis (PCA). Plants which were cultivated in soil under greenhouse conditions were subjected to four levels foliar spraying of Zargreen liquid organic fertilizer, ZLOF (0, 2.5, 5, and 7.5 L 1000−1, shown as Z0, Z2.5, Z5, and Z7.5, respectively), and three levels of soil water, SW (100, 75, and 50% of field capacity (FC), shown W100, W75, and W50, respectively). The results of biplot analysis using the different treatments representing 42.9% and 38.3%, 60.3% and 28.8%, and 63.1% and 22.4% of the variance attributed to the first two principal components (PCs) for the PC1 and PC2, under 100, 75, and 50% FC conditions, respectively. Water deficit induced a reduction of fruit dry, and fresh weights. Application of 2.5, 5, and 7.5 L 1000−1 of the organic fertilizer significantly increased fruit fresh weight by 16, 20, and 22% and fruit dry weight by 13, 20, and 20% as compared to that of control, respectively. Vitamin C content of fruit significantly increased by 16 and 33% when respectively 5 and 7.5 L 1000−1 of the organic fertilizer was foliar sprayed. Besides, fruit iron (Fe), sodium (Na (and potassium (K) concentrations increased with the application of the organic fertilizer at different levels of water deficit. Furthermore, the highest fruit zinc (Zn) concentration was obtained at the highest level of both applied organic fertilizer and water deficit. The best treatments were selected with increased PC1 and decreased PC2 for different water conditions. The W100Z7.5, W75Z7.5, and W50Z5 treatments with the higher PC1 and the lower PC2, also exhibited higher scores for fruit dry weight, and Na and K concentrations under W100; vitamin C, number of fruits, fruit fresh weight, and fruit Fe concentration under W75; citric acid, and fruit Fe, Zn, Na, K, and Cu concentrations under W50 treatment. The addition of the organic fertilizer was effective in enhancing the plant growth traits under water deficit conditions. Therefore, it can be concluded that organic fertilizer addition is an effective management strategy to mitigate the adverse effects of drought and improve the quantity and quality of tomato fruit.